Social gradient in intermediary determinants of oral health at school level in Finland - Anttila J; Tolvanen M; Kankaanpää R; Lahti S (F D I WORLD DENTAL PRESS LTD, 2022)
Objective: An adapted framework for oral health inequalities suggests that structural determinants cause oral health inequalities through socio-economic position (SEP) and intermediary determinants. We applied this framework to examine whether there is a social gradient in the intermediary determinants at the school level, even when adjusted for school size, geographical location and teaching language.
Basic research design: Cross-sectional survey. Methods: This study combined data from two independent studies focusing on Finnish upper comprehensive schools (N=970): the School Health Promotion study (SHPS) and the School Sweet Selling survey (SSSS). All schools that took part in the SSSS and whose pupils answered the SHPS were included in the analysis (n=360, response rate=37%). From the questions of the SHPS and the SSSS suitable for the theoretical framework, attitudes and access to intoxicants, school health services, school environment, home environment, the school's oral health-related actions and the pupil's own behaviour were selected as the intermediary determinants and as the factors determining the school-level SEP. The social gradient in the intermediary determinants of oral health was investigated with Pearson's and Spearman's correlation coefficients between those and the school-level SEP. In the multivariable analysis, the General Linear Model with manual backward elimination was used.
Results: A social gradient was observed in the intermediary determinants 'home environment' and 'the pupils' tooth brushing frequency' and an inverse social gradient in 'attitudes and access to intoxicants' and 'school health services'.
Conclusions: Social gradient between schools could increase Finnish adolescents' oral health inequalities.